ISOLATION AND STRUCTURE ELUCIDATIONS OF RESVERATROL OLIGOMERS FROM STEM BARK OF Dryobalanops lanceolata - Sahidin Sahidin (Indonesian Journal of Chemistry, 2009)
Five resveratrol oligomers which consist of two resveratrol dimers, balanocarpol (1) and ε-viniferin (2), α resveratrol trimer i.e. α-viniferin (3), and two resveratrol tetramers, vaticanol B (4), and hopeaphenol (5) have been isolated from acetone extract of the stem bark of Dryobalanops lanceolata. These compounds were isolated by vacuum liquid chromatography method. Furthermore, the compound structures were determined based on the spectroscopic evidence, including UV, IR, 1-D and 2D NMR spectra, and comparing with those related data reported previously.